High-performance PbS/CdS quantum dot Co-sensitized hierarchical ZnO nanowall photoanodes decorated on electrochemically reduced graphene. (10th January 2023) - Gür, Eftade Pınar; Eryiğit, Mesut; Demir, Ümit
Highlights: Electrochemically reduced graphene oxide (ERGO)/ZnO nanowalls (NWs) were prepared electrochemically. ZnONWs/ERGO were decorated with PbS and CdS QDs to fabricate co-sensitized quantum dot solar cells (QDSSC). The effect of single, co-sensitization, and QD sequencing on cell performance was investigated. PbS/CdS co-sensitized ERGO/ZnONWs photoelectrode shows high performance with η of 5.85%. Abstract: In this study, we report the vertically aligned ZnO nanowalls (NWs) decorated electrochemically reduced graphene oxide (ERGO) structures co-deposited directly on the FTO substrates by a simple and one-pot electrochemical technique. Then, these ERGO/ZnONWs were co-sensitized with a successive layer of PbS and CdS quantum dots (QDs) by a successive ionic layer adsorption and reaction (SILAR) technique for the fabrication of ERGO/ZnONWs/PbS/CdS photoelectrodes. The effect of the number of PbS and CdS SILAR cycles on the photocurrent response of ERGO/ZnONWs photoelectrodes was systematically investigated by varying the SILAR cycle number. The QDSSCs were fabricated by using the PbS, CdS and PbS/CdS QDs decorated ERGO/ZnONWs as photoelectrode, copper (I) sulfide (Cu2 S) as the counter electrode, and polysulfide redox couple (S 2− /Sx 2− ) as an electrolyte. Compared with ERGO/ZnONWs photoelectrode sensitized with single QDs (PbS or CdS), the PbS/CdS co-sensitized ERGO/ZnONWs photoelectrodes showed the best performance with efficiency (η) of 5.85%, open-circuit voltage ( Voc ) of 0.65 V, a short circuit current density ( Jsc ) of 23.01 mA.cm −2, and a fill factor ( FF ) of 0.39 under one sun illumination, which is relatively higher than other PbS/CdS co-sensitized ZnO based QDSSCs previously reported in the literature. In this cascaded FTO-ERGO/ZnONWs/PbS/CdS, CdS serves as a passivating layer to PbS and contributes light absorption and highly efficient injection of electrons from CdS to PbS and then to ZnO due to its higher CB band. The present study also highlights the potential of this novel ERGO/ZnONWs/PbS/CdS photoanode. It introduces simple, green, and economical electrochemical techniques for researchers interested in fabricating ERGO/ZnONWs for various applications. Graphical abstract: Image, graphical abstract